Numerical Investigation of the Ion Cyclotron Resonance Heating (ICRH) Physics in DTT. Issue 1 (1st December 2022) - Cardinali, A.; Baiocchi, B.; Castaldo, C.; Bilato, R.; Brambilla, M.; Casiraghi, I.; Ceccuzzi, S.; Napoli, F.; Ravera, G. L.; Tuccillo, A. A.
Abstract: An extensive linear analysis of the ICRH propagation and absorption in DTT full heating scenario has been performed by means of three advanced numerical tools: DISEMAG, FELICE and TORIC. The numerical codes solve respectively the full dispersion relation in the complex domain of the wavenumber (DISEMAG) and the integro-differential equation that accounts for the correct evaluation of the ICRH power absorption in a slab plasma (FELICE) and in the tokamak equilibrium configuration (TORIC). Moreover, by incorporating the antenna conceptual design, as released by the engineering design team, in FELICE and TORIC, the power spectrum, radiated by the antenna (3 straps) and coupled to the plasma, has been evaluated in the case of 60 and 90 MHz ( 3 He and H minority heating respectively). By extensively using the abovementioned suite of codes, and after establishing the plasma target (fixing tokamak dimensions, density, temperatures, plasma current, magnetic field, isotopic composition, etc.), and the antenna characteristics (number, dimension, pitch, and radial position of the straps, antenna size, etc.), the power absorption on the various species (electrons, majority and minority ions) has been calculated as function of the minority concentration, parallel wavenumber, frequency, harmonic resonant layer, etc.. Comparison between the codes DISEMAG and TORIC in evaluating the absorption on electrons and minority ions has also been performed and shows a good agreement of the results. A new ion heating scheme based on three ions mixture has also been proposed in DTT.